Performance management hurdles in a public health sector organisation in Zimbabwe - Mahapa, Mildred; Dzimbiri, L.; Maphosa, F. (Midlands State University, 2016)
Performance management has become widely recognised and accepted as a basic management tool. It greatly influences the levels of productivity, service delivery and the image of an organisation in general. However the implementation of performance management system and any other system in general can have its own challenges.The main aim of the research was to assess the challenges that public hospitals face in the implementation of their performance management system. The researcher conveniently selected one provincial hospital in Zimbabwe Purposive and systematic random sampling was used to select participants for the research. A total of 94 respondents participated in the research.Collection of data was done through questionnaires, interviews, observations and company records. The findings of the study reveal that the organization uses the Results Based Management system as its performance management tool and there are a number challenges being faced in the implementation of the system. The challenges include lack of motivation, lack of knowledge, insufficient human and financial resources, difficulties in identifying performance indicators and that there was no link between performance gapes and training programs. These challenges made it difficult for the hospital to enjoy the benefits, thereby impacting negatively on service delivery. The study recommends further training on how RBM is implemented and that resources be availed for the effective implementation of PM.